Persepsi Mahasiswa Akuntansi Terhadap Pemilihan Profesi Akuntan Publik : Studi Kasus:Mahasiswa Program Studi Akuntansi Angkatan 2021 Universitas HKBP Nommensen Medan - Lili Permatasari; Ardin Dolok Saribu; Mangasa Sinurat (Jurnal Minfo Polgan, 2025)
This study aims to determine the Perception of Accounting Students that influence the Selection of a Profession to Become a Public Accountant. This research was conducted using a quantitative research type. This study uses primary data where this study uses a survey in the form of a questionnaire. The population determined in this study were Accounting Students of the 2021 batch of HKBP Nommensen University Medan.This study uses a quantitative method to test the perception of accounting students whether it influences the selection of a profession to become a public accountant using simple linear regression analysis. Sampling in this study used the purposive sampling method. The data used in this study are primary data in the form of respondents' answers to the questionnaire used in the study. The analysis methods used in this study are descriptive statistics, reliability and validity tests, classical assumption tests, simple linear regression analysis, hypothesis testing and coefficient of determination (R-square).The results of this study indicate that the Perception of Accounting Students has a positive and significant effect on the Selection of the Public Accountant Profession.